Shift work and incident atrial fibrillation in younger and older individuals. (19th May 2022) - Zwartkruis, VW; Lochen, ML; De Boer, RA; Mathiesen, EB; Njolstad, I; Wilsgaard, T; Sharashova, E; Rienstra, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Shift work is associated with myocardial infarction and stroke. However, comparatively little is known about the association between shift work and atrial fibrillation (AF). Purpose: We aimed to study if shift work is associated with incident AF, and if this association differs depending on sex and age. Methods: We studied 22 339 participants (age 37±10 years, 49% women) with paid work and without prevalent AF from the third (1986-1987), fourth (1994-1995), fifth (2001), and sixth (2007-2008) survey of the population-based Tromsø Study. AF was ascertained by searching participants' hospital records for AF events, which were further adjudicated by an endpoint committee. All AF was ECG-confirmed. Follow-up for AF was available through 2016. Shift work status was assessed by questionnaire at each survey. If participants attended multiple surveys, the first attended survey was considered the baseline visit. We used Cox regression models (unadjusted, age- and sex-adjusted, and multivariable-adjusted) to study the association of shift work at baseline with (1) incident AF during the first 10 years of follow-up and (2) incident AF during the total follow-up period (through 2016). Interactions with sex and age were tested in the multivariable model. Analyses were stratified when a significant interaction (p for interaction <0.10) was present. Results: Shift work was reported by 21% of participants at baseline. Participants with shift work were younger and had a lower average education level, lower prevalence of hypertension, higher BMI, and higher prevalence of smoking than those without shift work. During the first 10 years of follow-up, 129 participants (0.6%) developed AF. Shift work was not significantly associated with 10-year incident AF in any of the models. There was no interaction between shift work and sex (p for interaction = 0.687). However, there was a significant interaction between shift work and age (p for interaction = 0.059). In participants aged <40 years, shift work was significantly associated with 10-year incident AF in the unadjusted model (HR 2.65, 95% CI 1.05-6.71) and age- and sex-adjusted model (HR 2.71, 95% CI 1.07-6.88), but not in the multivariable model (HR 2.37, 95% 0.91-6.17). In participants aged ≥40 years, shift work was not associated with 10-year incident AF (Table 1). During the total follow-up (22±10 years), 1244 participants (5.6%) developed AF. When considering the total follow-up duration, shift work was not significantly associated with AF in any model, and none of the interaction terms with age or sex were significant. Conclusions: In the total study population, shift work was not associated with incident AF. However, our results indicate that shift work may be associated with 10-year risk of AF in younger individuals.